2016
DOI: 10.1111/raq.12163
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C supplementation to optimize growth, health and stress resistance in aquatic animals

Abstract: Vitamins are organic compounds that can be synthesized from other essential nutrients; however, they are required in trace amounts from an exogenous source for normal growth, reproduction and health. Vitamin C (ascorbic acid, AA) is an essential micronutrient for normal growth and physiological function of most aquatic animals. In terrestrial animal nutrition, vitamin C has recently spurred scientific interest because of the increasing knowledge on vitamin C involvement in gene expression, cell cycle and repro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 184 publications
(190 reference statements)
3
113
1
2
Order By: Relevance
“…Food additives are important for animal nutrition because they help to improve animal performance, health and the quality of their final products (Ribeiro et al, ). Several additives have been used for tilapia at various stages in order to improve growth, survival and animal health (Dawood & Koshio, , ; Dawood, Koshio, Abdel‐Daim, & Van Doan, ; Dawood, Koshio, & Esteban, ; Freccia et al, ; Schwarz, Furuya, Natali, Gaudezi, & Lima, ; Schwarz, Furuya, Natali, Michelato, & Gaudezi, ), including bee pollen (Abbass et al, ; El‐Asely et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food additives are important for animal nutrition because they help to improve animal performance, health and the quality of their final products (Ribeiro et al, ). Several additives have been used for tilapia at various stages in order to improve growth, survival and animal health (Dawood & Koshio, , ; Dawood, Koshio, Abdel‐Daim, & Van Doan, ; Dawood, Koshio, & Esteban, ; Freccia et al, ; Schwarz, Furuya, Natali, Gaudezi, & Lima, ; Schwarz, Furuya, Natali, Michelato, & Gaudezi, ), including bee pollen (Abbass et al, ; El‐Asely et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…additives are important for animal nutrition because they help to improve animal performance, health and the quality of their final products(Ribeiro et al, 2012). Several additives have been used for tilapia at various stages in order to improve growth, survival and animal health(Dawood & Koshio, 2016a, 2016bDawood, Koshio, Abdel-Daim, & Van Doan, 2018;Dawood, Koshio, & Esteban, 2017;Freccia et al, 2016;Schwarz, Furuya, Natali, Gaudezi, & Lima, 2011;Schwarz, Furuya, Natali, Michelato, & Gaudezi, 2010), including bee pollen(Abbass et al, 2012;El- Asely et al, 2014).For example, Abbass et al (2012) evaluated bee pollen as a feed additive and its effects on zootechnical performance of Nile tilapia (~45 g) in an open system with continuous water exchange. The authors found that 2.5% of propolis or pollen in the diets improved the specific growth rate, average daily gain, and feed efficiency of tilapia.…”
mentioning
confidence: 99%
“…Moreover, National Research Council (NRC) () reported that vitamin C is important in growth, collagen formation, iron metabolism and haematology, reproduction, response to stressors, wound healing and immune response. Also, Dawood, () mentioned that most aquatic animals need vitamin C for their normal growth and physiological functions. In the present study, we recorded improvement in group III in which vitamin C was supplemented.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C is one of the important nutrients because it is a powerful antioxidant and immunomodulator for fish/shrimps. The fish and shrimp body need vitamin C to remain proper health condition (Dawood & Koshio 2016b). Vitamin C has been known to be an important micronutrient correlating with enhanced aquatic animal performances (Gao et al .…”
Section: Vitaminsmentioning
confidence: 99%